2018
DOI: 10.1530/erc-18-0050
|View full text |Cite
|
Sign up to set email alerts
|

TERT aberrancies: a screening tool for malignancy in follicular thyroid tumours

Abstract: Telomerase reverse transcriptase () promoter mutations have been linked to adverse clinical parameters in thyroid cancer, but -expressing tumours are not always mutated. Little is known regarding other-related genetic aberrations. To delineate the role of gene aberrancies in follicular thyroid tumours, 95 follicular carcinomas (FTCs), 43 follicular adenomas (FTAs) and 33 follicular tumours of uncertain malignant potential (FT-UMPs) were collected. The tumours were assayed for expression, promoter mutations, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 27 publications
6
62
1
Order By: Relevance
“…Compared with other clinicopathological features, the TERT promoter mutations possibly make more contribution to distant metastasis and advanced TNM stage of DTC, especially to distant metastasis of FTC (OR = 24.29). As described in nearly all the relevant literature on prognosis [16,20,26,67], our metaanalysis showed that TERT promoter mutations were strongly associated with persistence/recurrence, and disease-specific mortality, and indicated that patients with TERT promoter mutations in FTC also have poor prognosis. Thus, TERT promoter mutations may be considered biomarkers for prognosis in FTC.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Compared with other clinicopathological features, the TERT promoter mutations possibly make more contribution to distant metastasis and advanced TNM stage of DTC, especially to distant metastasis of FTC (OR = 24.29). As described in nearly all the relevant literature on prognosis [16,20,26,67], our metaanalysis showed that TERT promoter mutations were strongly associated with persistence/recurrence, and disease-specific mortality, and indicated that patients with TERT promoter mutations in FTC also have poor prognosis. Thus, TERT promoter mutations may be considered biomarkers for prognosis in FTC.…”
Section: Discussionsupporting
confidence: 62%
“…In FTC, the average frequency of TERT promoter mutations was 15.1%, which was higher than that in PTC. The majority of the studies reported TERT promoter mutations were not detected in FTA [16,67,69,71]. However, a current case report study showed TERT promoter (C228T) mutation in a patient with FTA [70].…”
Section: Discussioncontrasting
confidence: 52%
“…Due to the unavailability of mRNA samples, we could not study directly the effects of CNV on TERT mRNA expression. However, other studies have shown the association between TERT copy number gain and mRNA expression in several cancer types, including FTC . Nevertheless, larger studies, particularly those focusing on advanced thyroid cancers, are required to provide definitive confirmation of this mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Reactivation of telomerase in human malignancies has also been linked to TERT amplification . In fact, the TERT gene locus was found to be amplified in various cancers including lung, breast, cervical carcinomas, and FTC, prompting us to examine the TERT gene for copy number alterations in different types of thyroid cancer. Interestingly, we observed that the increase in TERT locus copy number was more common in FTC, HCC, and PDTC, as compared to PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation